Calreticulin: a multifunctional protein with potential therapeutic applications for chronic wounds - Sawaya, Andrew P.; Vecin, Nicole M.; Burgess, Jamie L.; Ojeh, Nkemcho; DiBartolomeo, Gabrielle; Stone, Rivka C.; Pastar, Irena; Tomic-Canic, Marjana (Frontiers in Medicine, 2023)
Calreticulin is recognized as a multifunctional protein that serves an essential role in diverse biological processes that include wound healing, modification and folding of proteins, regulation of the secretory pathway, cell motility, cellular metabolism, protein synthesis, regulation of gene expression, cell cycle regulation and apoptosis. Although the role of calreticulin as an endoplasmic reticulum-chaperone protein has been well described, several studies have demonstrated calreticulin to be a highly versatile protein with an essential role during wound healing. These features make it an ideal molecule for treating a complex, multifactorial diseases that require fine tuning, such as chronic wounds. Indeed, topical application of recombinant calreticulin to wounds in multiple models of wound healing has demonstrated remarkable pro-healing effects. Among them include enhanced keratinocyte and fibroblast migration and proliferation, induction of extracellular matrix proteins, recruitment of macrophages along with increased granulation tissue formation, all of which are important functions in promoting wound healing that are deregulated in chronic wounds. Given the high degree of diverse functions and pro-healing effects, application of exogenous calreticulin warrants further investigation as a potential novel therapeutic option for chronic wound patients. Here, we review and highlight the significant effects of topical application of calreticulin on enhancing wound healing and its potential as a novel therapeutic option to shift chronic wounds into healing, acute-like wounds.